Word-initial trill clusters in children with typical versus protracted phonological development: Bulgarian. (4th May 2018) - Ignatova, Diana; Bernhardt, Barbara May; Marinova-Todd, Stefka; Stemberger, Joseph Paul
ABSTRACT: The current paper describes acquisition of word-initial (WI) trilled /r/ in clusters and as a singleton in 60 Bulgarian 3–5-year-olds with typically developing (TD) versus protracted phonological development (PPD). A native speaker audio-recorded and transcribed single-word responses to a picture-naming task (110 words) that included eight words with WI rhotic clusters and two with WI singleton /r/. Accuracy was significantly higher in the TD groups and for the PPD groups, by age. Mismatch patterns varied: the PPD cohort had the most varied patterns although the younger children with PPD showed more /r/ deletion in clusters, and the TD groups and 5-year-olds with PPD more substitutions for /r/. Substitutions for rhotics included taps (most frequent; possibly an acceptable variant), voiced uvular and palatal fricatives, laterals, glides, other rhotics, stops and nasals. These results add to the growing database on Bulgarian phonological acquisition concerning accuracy and mismatches by group and age.